Can public–private partnership investment in energy (PPPI) mitigate CO2 emissions in South Africa? Fresh evidence from the novel dynamic ARDL simulations approach - Udeagha, Maxwell Chukwudi; Ngepah, Nicholas (Frontiers in Environmental Science, 2023)
Global warming is presenting a worrisome condition that necessitates important actions across the planet. One promising strategy is to encourage investments through Public-Private Partnership Investment (PPPI) in green ventures. The Environmental Kuznets Curve (EKC) hypothesis framework is used in the current study to examine the relationship between the aforementioned factor and the level of carbon dioxide (CO2) emissions for South Africa between 1960 and 2020. Using the recently developed novel dynamic autoregressive distributed lag (ARDL) simulations framework, the results showed that: (i) public-private partnerships investment in energy contribute to deteriorate environmental quality; (ii) while technique effect improves environmental quality, the scale effect largely contributes to escalate CO2 emissions, thus confirming that the EKC hypothesis holds; (iii) energy consumption, foreign direct investment, trade openness, and industrial growth escalate CO2 emissions but technological innovation reduces it; (iv) public-private partnerships investment in energy, technological innovation, scale effect, technique effect, foreign direct investment, energy consumption, industrial growth, and trade openness Granger-cause CO2 emissions in the short, medium and long run showing that these variables are fundamental to determine environmental quality. Our empirical findings suggest that PPPIs should be accomplished in environmentally friendly sectors and industries, and also South Africa’s government and policymakers should take further initiatives to ensure the implementation of policies, which enable the change from non-renewable energy sources to renewable ones to promote efficiency in the production processes and curtail CO2 emissions in the country.